POOR ACEH: THE IMPACT OF SPECIAL AUTONOMY AS EFFORT POVERTY REDUCTION IN ACEH - Deni Setiawan; Khalida Ulfa; Titin Purwaningsih (DIA: Jurnal Administrasi Publik, 2020)
Special autonomy as one of the strategies in overcoming social welfare issues is one of them in Aceh Province. The implementation of regional autonomy after the reforms marked by the issuance of Law Number 33 of 2004 concerning the financial balance between the central government to the regions. The hope is to make the regions more autonomous or independent in government, and a more equal financial structure and the right to manage financial resources that are more transparent. This research focuses on the impact of the implementation of special autonomy in Aceh Province, limited from 2015 to 2019 in poverty alleviation efforts. This study uses a qualitative method with a descriptive approach to literature study and statistical data analysis. Data analysis techniques in this study were using statistical data analysis obtained from BPS. The results showed that special autonomy as an effort to reduce poverty in Aceh has a very good contribution because it has reduced poverty in Aceh from 819 thousand in March 2019 to 810 thousand people in September 2019. And the use of the special autonomy fund was channeled through programs made by the Aceh government in the fields of Education, Health, and the economy.